DEVELOPMENT OF DIORAMA MEDIA TO INCREASE THE LEARNING INTEREST OF CLASS IV STUDENTS WITH IPS CONTENT - Setiani, Opi Ingguh; -, Supriansyah - (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research aims to develop a media Diorama of IPS subject content livelihood material based on the landscape in grade IV elementary school. The method used in this study was Research and Development model ADDIE. This research was conducted at SDN Susukan 05 Pagi, class IV as many as 25 people. The data collection methods in this study used validation charts aimed at media experts and material experts, and response charts and learning interests aimed at the students who were the subjects of this study. Media expert validation results came in the